Reimagining the role of mentor teachers in professional experience: moving to I as fellow teacher educator. Issue 4 (8th August 2018) - Grimmett, Helen; Forgasz, Rachel; Williams, Judy; White, Simone
ABSTRACT: New accreditation requirements for Australian initial teacher education programs require that universities and schools establish quality partnerships to ensure strong links between pre-service teachers' university-based learning and school-based professional learning experiences. This paper focuses on the shifts of identity, thinking and practice that occurred for five school-based mentor teachers as they co-created new professional experience practices alongside university-based teacher educators in a Teaching Academies of Professional Practice (TAPP) project. Interview data was analysed through the theoretical framework of Dialogical Self Theory to examine how the repositioning of mentor teachers as fellow teacher educators allowed for expansion in the understanding and enactment of their role. The findings of this study suggest that partnerships between schools and universities can enhance learning opportunities for all participants when commitments are made to creating collaborative and dialogical spaces to support new approaches to teacher education.